A critical overview of the current myofascial pain literature – March 2017. Issue 2 (April 2017) - Dommerholt, Jan; Grieve, Rob; Hooks, Todd; Finnegan, Michelle
Abstract: After two years of having contributed to this overview series of articles, we sadly say goodbye to Dr. Rob Grieve. We would like to thank Dr. Grieve for his insightful contributions and analyses of the myofascial pain literature. Dr. Grieve would have preferred to continue, but his many university and research responsibilities had to take priority. We are looking forward to reviewing his future research endeavors in this article. We are pleased that Dr. Li-Wei Chou, MD, PhD has agreed to replace Dr. Grieve and join our team. Dr. Chou is Assistant Professor at China Medical University in Taichung, Taiwan and he has an impressive publication record with many research studies and book chapters. In this edition of the overview article, we once again have included articles from around the world with a combination of basic research and clinical studies and case reports. The majority of papers deal with dry needling, but there are also several more basic research studies and manual therapy papers.